Landslide susceptibility analysis on road sections in Kaligesing District, Indonesia, using Frequency Ratio (FR) approaches - Rianita Pertiwi; Junun Sartohadi; M. Anggri Setiawan; Edwin Maulana (Journal of Degraded and Mining Lands Management)
Road construction with intensive slope cutting increases landslide susceptibility along the road section, especially in hilly areas such as Kaligesing, Indonesia. This study aimed to compile a landslide susceptibility map along the road section in Kaligesing and evaluate the level of susceptibility based on the main causal factors. GIS approach and quantitative statistical analysis Frequency Ratio (FR) were used in the susceptibility model. Eighty-two landslide points were randomly divided into training (70%) and testing (30%) datasets. Twelve causal factors were used in the analysis: slope direction, elevation, lithology, slope gradient, curvature, hemeroby degree, Topographic Wetness Index (TWI), distance from the river, distance from the road, rainfall, soil texture, and soil aggregate. Model validation used the Area Under Curve (AUC) value to evaluate model performance. The findings showed that the model is accurate, with an AUC value of 0.75 for the training set and 0.71 for the testing set. Furthermore, the level of landslide susceptibility is divided into four classes, namely very high (73 km), high (70.77 km), moderate (0.07 km), and very low (0.03 km). Thus, the findings can be used to support decision-making and planning for more adaptive road infrastructure development in landslide-prone areas.